Palladium-Catalyzed Synthesis of Ammonium Sulfinates from Aryl Halides and a Sulfur Dioxide Surrogate: A Gas- and Reductant-Free Process** - Emmett, Edward J (Angew Chem Int Ed Engl, 2014)
Sulfonyl-derived functional groups populate a broad range of useful molecules and materials, and despite a variety of preparative methods being available, processes which introduce the most basic sulfonyl building block, sulfur dioxide, using catalytic methods, are rare. Described herein is a simple reaction system consisting of the sulfur dioxide surrogate DABSO, triethylamine, and a palladium(0) catalyst for effective convertion of a broad range of aryl and heteroaryl halides into the corresponding ammonium sulfinates. Key features of this gas- and reductant-free reaction include the low loadings of palladium (1 mol %) and ligand (1.5 mol %) which can be employed, and the use of isopropyl alcohol as both a solvent and formal reductant. The ammonium sulfinate products are converted in situ into a variety of sulfonyl-containing functional groups, including sulfones, sulfonyl chlorides, and sulfonamides.